Superiority of Azadirachtin Over Other Bio Chemical Active Compounds in Controlling Nuclear Polyhedrosis (Grasserie Disease) of Silkworm, Bombyx Mori Linnaeus - Deb, Suman; Sinha, Ajit Kumar; Saha, Atul Kr.; Chakraborty, Satadal (Journal of Agricultural Policy, 2023)
Purpose: The study was focused on to find out most cost-effective, user-friendly bio active chemicals among available one to control Grasserie. Methodology: Simple rearing (both favourable and unfavourable rearing season) and dusting method. Findings: Azadirachtin is more effective among other active biochemical counterparts. Unique Contribution to Theory, Policy and Practice: As traditionally available disinfectants are of high cost and hazardous to its user as well to the environment, this type study is unique in its application and investigation. The Allicin and Curcumin were found to be similar in action in comparison to Azadirachtin particularly in unfavourable rearing season. However, Azadirachtin was found to be more effective in both favourable and unfavourable rearing season in comparison to its other counterparts.